Stem Cell Smart Technology, where are we now and how far we have to go?. (April 2018) - Sultan, Sherif; Kavanagh, Edel P; Michalus, Robert; Hynes, Niamh
Approximately eight million people in the United States have peripheral arterial disease, which increases exponentially with age. There have been a plethora of available treatments including surgery, angioplasty, atherectomy, laser technology, and cell-based therapies. Cell-based therapies were developed in the hope of translating laboratory-based technology into clinical successes. However, clinical results have been disappointing. Infusion or injection for stem cell therapy is still considered experimental and investigational, and major questions on safety and durability have arisen. In no option patients, how can they be treated safely and successfully? In this article, we review contemporary practice for cell therapy, its pitfalls and breakthroughs, and look at the future ahead. We introduce a novel smart system for minimally invasive delivery of cell therapies, which exemplifies the next generation of endovascular solutions to stem cell technology and promises safety, efficacy, and reliability.